A Bama miniature pig model of monoallelic TSC1 mutation for human tuberous sclerosis complex. (20th December 2020) - Li, Xiaoxue; Hu, Tingdong; Liu, Jiying; Fang, Bin; Geng, Xue; Xiong, Qiang; Zhang, Lining; Jin, Yong; Liu, Xiaorui; Li, Lin; Wang, Ying; Li, Rongfeng; et al.
Abstract: Tuberous sclerosis complex (TSC) is a dominant genetic neurocutaneous syndrome characterized by multiple organ hamartomas. Although rodent models bearing a germline mutation in either TSC1 or TSC2 gene have been generated, they do not develop pathogenic lesions matching those seen in patients with TSC because of the significant differences between mice and humans, highlighting the need for an improved large animal model of TSC. Here, we successfully generate monoallelic TSC1 -modified Bama miniature pigs using the CRISPR/Cas9 system along with somatic cell nuclear transfer (SCNT) technology. The expression of phosphorylated target ribosomal protein S6 is significantly enhanced in the piglets, indicating that disruption of a TSC1 allele activate the mechanistic target of rapamycin (mTOR) signaling pathway. Notably, differing from the mouse TSC models reported previously, the TSC1 +/− Bama miniature pig developed cardiac rhabdomyoma and subependymal nodules, resembling the major clinical features that occur in patients with TSC. These TSC1 +/− Bama miniature pigs could serve as valuable large animal models for further elucidation of the pathogenesis of TSC and the development of therapeutic strategies for TSC disease.